Dynamics of Changes in the Level of Cognitive Functioning Among Patients After SARS-CoV-2 Infection ‒ A Proposal for Remote Neuropsychological Assessment in a Longitudinal Study - Malinowska, Ewa; Żarnecka, Dominika; Łojek, Emilia; NeuroCovid Research Team (Przegląd Psychologiczny, 2024)
Study purpose: The aim of this longitudinal study was to assess the cognitive functioning of people who had COVID-19, to determine the dynamics of changes observed in this area over a period of 3‒4 months, to compare the patients’ results with those of a control group, and to verify the usefulness of a new method of remote neuropsychological assessment. Method: A longitudinal study was conducted using the Brief Test of Adult Cognition by Telephone (BTACT) neuropsychological assessment tool, which was translated into Polish for the purpose of the study. The study included subjects following SARS-CoV-2 infection (COVID(+) group) and control subjects (COVID(‒) group). Cognitive functions in both groups were assessed twice, 3‒4 months apart. The study was conducted from July 2020 to January 2022. Results: Data comparisons were performed using mixed ANOVA with repeated measures. Compared to the COVID(‒) group, the COVID(+) group scored significantly lower on the first and second measurements of the Backward Digit Span Test and on the first measurement of the Number Series Test. Additionally, an improvement was observed in COVID(+) group scores in the second measurement compared to the first measurement in: Rey Auditory-Verbal Learning Test (RAVLT) in both the immediate and delayed recall condition; the Backward Digit Span Test, the Number Series Test and 30 Seconds and Counting Task (30-SACT). Conclusions: The obtained results show an impairment in working memory functions and inductive reasoning in COVID(+) subjects compared to COVID(‒) subjects. In addition, the study indicates the usefulness of BTACT in tracking the changes in cognitive functioning over time in individuals following SARS-CoV-2 infection. Tests to assess working memory (Rey Auditory-Verbal Learning Test (RAVLT), Backward Digit Span Test) and a test of inductive reasoning (Number Series Test) appear to be particularly useful in monitoring the mentioned changes.